REGENERATION OF AN AFROMONTANE FOREST FOLLOWING AGRICULTURAL ENCROACHMENT IN SOUTHWESTERN UGANDA - LEJJU, JULIUS BUNNY; ORYEM-ORIGA, HANNINGTON; KASENENE, JOHN M (Israel Journal of Plant Sciences, 2015)
A study of the regeneration of an Afromontane forest was carried out in Mgahinga Gorilla National Park (MGNP), southwestern Uganda, following agricultural encroachment in the last 50 years. The landscape was changed by terracing and removing the indigenous vegetation and replacing it with exotic tree species. This study also examined the soil nutrient status of the formerly encroached area in the park. Species richness of indigenous trees was high in the formerly cultivated area. Twenty-six indigenous species were found in the formerly cultivated area, compared with 20 species in the natural forest and 12 species of indigenous trees found under exotic woodlots. There was a significant difference in species richness and density in the three habitat types. The natural forest supported the highest stem density (75%), and the lowest stem density (4%) was recorded under exotic woodlots. Seedlings (<2 cm diameter at breast height) accounted for the majority of juveniles in the three habitats. The natural forest had the highest density (24,625 seedlings/ha), and exotic woodlots supported the lowest stem density (1,350 seedlings/ha). The level of regeneration in the formerly encroached area is influenced by the intensity of cultivation and soil nutrients. The advanced growth beneath the exotic woodlots, especially black wattle (Acacia mearnsii) and Eucalyptus sp. stands, is relatively impoverished. This condition beneath the exotic species suggests that a low diverse community of native species is able to exploit this environment.
Keywords: REGENERATION; AFROMONTANE FOREST; FOREST; AGRICULTURAL ENCROACHMENT; SOUTHWESTERN UGANDA